Developing an Interactive HTML5-Based Game for Tenses Learning for Senior High School Students - Faza Hannan Purinanda (Universitas Negeri Yogyakarta, 2020)
This research study aims at developing an interactive HTML5-based game to facilitate senior high school students in learning tenses. This research is a research and development study. The development of the game is carried out through several steps, which are needs analysis, outline of materials design, product development, expert judgement, product revision, and final product development. The result of this study is a web-based game titled The Time Traveller. Based on the results of expert judgement, the game is appropriate for senior high school students based on the mean scores of 3.52, which is in the range of 3.25 ≤ x ≤ 4 and falls into the category of “Very Good.”